Desain Partisipatif Interior Ruang Rapat, Podcast, dan Pantry Kantor Desa Cimenyan, Kabupaten Bandung, Jawa Barat - Santri, Tyas; Aditya, Nova Chandra; Primasetra, Anjar; Pamungkas, Girhan Ramdan; Safaat, Firda (Jurnal Pengabdian Tri Bhakti, 2025)
Cimenyan Village, located in Cimenyan Subdistrict, Bandung Regency, West Java, serves as a partner village for Langlangbuana University. The university's role involves collaborating with the village to address various local challenges. One such issue, as identified by village officials, is the absence of reference designs for the interiors of three new rooms in the Village Office building. To tackle this, a community service initiative titled "Developing Interior Design Plans for the Meeting Room, Podcast Room, and Pantry of Cimenyan Village Office, Cimenyan Subdistrict, Bandung Regency, West Java, Through User Participation" has been proposed. This program aims to create physical spaces that effectively support user activities by engaging architectural experts, local government partners, and active user involvement. The process encompasses several stages, including preliminary studies for initial understanding, participatory discussions to gather user input, conceptual design development reflecting user needs, and the preparation of detailed interior planning documents. This collaborative approach ensures that the resulting designs are both aesthetically pleasing and functional, tailored to the specific requirements of the users. Consequently, the meeting room, podcast room, and pantry are designed with a focus on comfort, efficiency, and the enhancement of productivity within the Cimenyan Village Office.